From Bhutan, with Love : Exploring the Perceptions of Bhutanese Students Studying Tourism and Hospitality in an Indian University - Kaushal, Vikrant; Sharma, Suman; Srivastava, Sidharth; Ali, Nurmahmud (Prabandhan: Indian Journal of Management, 2017)
The paper explored the perceptions of Bhutanese students studying tourism and hospitality in a private Indian university. Interviews with 21 students enrolled in ’Airlines, Tourism and Hospitality’ degree program were conducted followed by focus group. The study explored the participants’ perceptions about India, motivation to study tourism, viewpoints on the way of teaching, use of information technology in academics, and language at the place of study. The findings revealed that participants mostly held unfavourable pre-departure (prior) perceptions about the country, which eventually transformed to more favourable as the interface with the place of study grew. Participants’ interest in the program could be attributed to the appeal towards tourism, especially in the hopes of a career in airlines. They also perceived the program to be more theoretical than practical and more inclined towards hospitality learning rather than tourism. Perceptions of information technology used in the university were positive and participants acknowledged challenges related to the language in the place of study.